Blurring boundaries: An emotionally aware caregiver, social worker, and researcher. (September 2016) - Camacho, David
In this article, I illustrate lived experiences within my roles as caregiver, clinical social worker, and researcher. Empirical attention has focused on the emotional toll of caregiving and management of emotions as clinical social workers, however, little attention has been given to the impact emotions have on the researcher and how emotional awareness can be useful in the creation of knowledge. Using a personal reflexive account, I "out" myself as an emotionally aware caregiver, clinical social worker, and researcher. Finally, I provide examples of how to incorporate emotion into the research process.